Accuracy of five systems for self-monitoring of blood glucose in the hands of adult lay-users and professionals applying ISO 15197:2013 accuracy criteria and potential insulin dosing errors. (1st February 2019) - Jendrike, Nina; Baumstark, Annette; Pleus, Stefan; Liebing, Christina; Kamecke, Ulrike; Haug, Cornelia; Freckmann, Guido
Abstract: Objective: In this study, accuracy in the hands of intended users was evaluated for five self-monitoring of blood glucose (SMBG) systems based on ISO 15197:2013, and possibly related insulin dosing errors were calculated. In addition, accuracy was assessed in the hands of study personnel. Methods: For each system (Accu-Chek 1 Aviva Connect [A], Contour 2 Next One [B], FreeStyle Freedom Lite 3 [C], GlucoMen 4 areo [D] and OneTouch Verio 5 [E]) one test strip lot was evaluated as required by ISO 15197:2013, clause 8. Number and percentage of SMBG measurements within ±15 mg/dl and ±15% of the comparison measurements at glucose concentrations <100 mg/dl and ≥100 mg/dl, respectively, were calculated. In addition, data is presented in surveillance error grids, and insulin dosing errors were modeled. The study was registered at ClinicalTrials.gov (NCT03033849). Results: Four systems (A, B, C, D) fulfilled the tested reagent system lot ISO 15197:2013 accuracy criteria with the tested reagent system lot with at least 95% (lay-users) and 99.5% (study personnel) of results within the defined limits. Measurements with all five systems were within the clinically acceptable zones of the consensus error grid and the surveillance error grid. Median modeled insulin dosing errors were between -0.8 and +0.6 units for measurements performed by lay-users and between -0.7 and +0.8 units for study personnel. Frequent lay-user errors were not checking the test strips' expiry date, applying blood incorrectly and handling the device incorrectly. Conclusion: In this study, the systems showed slight differences in the number of results within ISO 15197:2013 accuracy limits. Inaccurate SMBG measurements can result in insulin dosing errors and adversely affect glycemic control. Trial registration: ClinicalTrials.gov identifier: NCT03033849.